Glycoprotein non-metastatic melanoma B expression after hepatic ischemia reperfusion and the effect of silibinin - Michalinos, Adamantios; Tsaroucha, Alexandra K.; Lambropoulou, Maria; Schizas, Dimitrios; Valsami, Georgia; Kostomitsopoulos, Nikolaos; Pitiakoudis, Michael S.; Simopoulos, Constantinos E. (Translational Gastroenterology and Hepatology, 2019)
Background: Glycoprotein non-metastatic melanoma B (GPNMB) is a transmembrane glycoprotein with various roles in inflammation regulation, tissue remodeling and oncogenesis. Clinical situations implicating alterations in its expression include ischemic injury, cirrhosis and fatty liver disease amongst other. We examine its expression in hepatic and renal tissue following hepatic ischemia-reperfusion (I/R) in a rat model, with and without intravenous silibinin administration, as a silibinin-hydroxypropyl-β-cyclodextrin lyophilized complex (SLB-HP-β-CD). Methods: Sixty-three Wistar rats were divided into 3 groups: sham group (virtual intervention; 7 animals), control (C) group (45 min of ischemia, followed by reperfusion and euthanasia at 60, 120, 180 and 240 min; 28 animals equally divided), and silibinin (Si) group (45 min of ischemia, intravenous administration of SLB-HP-β-CD, reperfusion and euthanasia at the same time points; 28 animals equally divided). GPNMB expression was examined in liver and kidney tissue. Results: GPNMB expression was significantly increased following hepatic I/R in the control group, in kidney tissue, in a time dependent manner. In the silibinin group, GPNMB expression significantly decreased with time compared to the control group in both liver and kidney tissue (P